Simulation and experimental study on the strength of Al7075-T6 clinched joint. (November 2021) - Xu, Honghe; Zhang, Yue; Peng, Ruitao; Zhu, Linwei; Lu, Yan
Highlights: The Johnson-Cook damage model was used to study the joint strength and failure mode. Compared with the experiment, the material flow in the simulation is more sufficient. The sheet fractured near the thinnest position in the neck, where the stress level was highest. The load is mainly caused by the friction of interlocking structure under peeling. The magnitude of the interlocking value determines the failure mode of the joint. Abstract: Al7075-T6 aluminum alloy has superior comprehensive performance, which is why it has been widely used in automotive, aerospace and other industries. In this paper, the clinched joint was studied by experiment and simulation. The finite element model of the clinching was established using ABAQUS. The clinching process and the forming mechanism of the joint were analyzed and studied. The Johnson-Cook damage model was used to simulate the tensile-shear and peel tests to study the joint strength as well as the failure mode. Based on the finite element simulation results and the experimental analysis, it was found that the lap joint failure mode was neck fracture failure. The upper sheet fractured near the clinched joint with a high stress level and the fracture location was at the weakest part of the neck. Under peeling conditions, the load is mainly caused by the friction between the two sheets and the interlocking structure, so the danger zone is located in the interlocking area of the upper sheet. The magnitude of the interlocking value determines whether the neck fracture failure or the neck pull-off failure occurs in the joint.